Abiotic stress responses in plants: roles of calmodulin-regulated proteins - Virdi, Amardeep S.; Singh, Supreet; Singh, Prabhjeet (Frontiers in Plant Science, 2015)
Intracellular changes in calcium ions (Ca2+) in response to different biotic and abiotic stimuli are detected by various sensor proteins in the plant cell. Calmodulin (CaM) is one of the most extensively studied Ca2+-sensing proteins and has been shown to be involved in transduction of Ca2+ signals. After interacting with Ca2+, CaM undergoes conformational change and influences the activities of a diverse range of CaM-binding proteins. A number of CaM-binding proteins have also been implicated in stress responses in plants, highlighting the central role played by CaM in adaptation to adverse environmental conditions. Stress adaptation in plants is a highly complex and multigenic response. Identification and characterization of CaM-modulated proteins in relation to different abiotic stresses could, therefore, prove to be essential for a deeper understanding of the molecular mechanisms involved in abiotic stress tolerance in plants. Various studies have revealed involvement of CaM in regulation of metal ions uptake, generation of reactive oxygen species and modulation of transcription factors such as CAMTA3, GTL1, and WRKY39. Activities of several kinases and phosphatases have also been shown to be modulated by CaM, thus providing further versatility to stress-associated signal transduction pathways. The results obtained from contemporary studies are consistent with the proposed role of CaM as an integrator of different stress signaling pathways, which allows plants to maintain homeostasis between different cellular processes. In this review, we have attempted to present the current state of understanding of the role of CaM in modulating different stress-regulated proteins and its implications in augmenting abiotic stress tolerance in plants.